Guiding Stem Cell Differentiation into Oligodendrocytes Using Graphene‐Nanofiber Hybrid Scaffolds. (26th March 2014) - Shah, Shreyas; Yin, Perry T.; Uehara, Thiers M.; Chueng, Sy‐Tsong Dean; Yang, Letao; Lee, Ki‐Bum
<x xml:space="preserve">Abstract</x> Graphene‐nanofiber hybrid scaffolds selectively guide the differentiation of neural stem cells into mature oligodendrocytes, which are the myelinating cells of the central nervous system. Moreover, this process is facilitated without introducing differentiation inducers into the culture media, underscoring the potential of a biomaterials‐approach for neural tissue engineering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>